2018
DOI: 10.1186/s12876-018-0765-3
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent common bile duct stones as a late complication of endoscopic sphincterotomy

Abstract: BackgroundEndoscopic retrograde cholangiopancreatography (ERCP) with endoscopic sphincterotomy (ES) has become well established as a modality for the management of common bile duct stones (CBDS), especially in the setting of associated cholangitis. Our study aims to determine the rate of long term morbidity of recurrent CBDS post ES.MethodsA retrospective analysis of patients who underwent ERCP and ES (ERCP+ES) was undertaken on a prospectively maintained database from 1998 to 2012 at the Northern Hospital, Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 23 publications
4
58
0
Order By: Relevance
“…GB left in situ with stones, which is a well‐known risk factor for CBDS recurrence, can be a cause of secondary CBDS migrated from GB, and cholecystectomy is recommended after endoscopic treatment for CBDS in cases with concurrent GB stones. Meanwhile, we believe the other two risk factors, a large bile duct and pneumobilia after treatment, can be a cause of primary CBDS as previously reported . Bile flow can be cholestatic in cases with a large common bile duct, and duodenobiliary reflux is present in cases with pneumobilia, both of which can develop primary CBDS.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…GB left in situ with stones, which is a well‐known risk factor for CBDS recurrence, can be a cause of secondary CBDS migrated from GB, and cholecystectomy is recommended after endoscopic treatment for CBDS in cases with concurrent GB stones. Meanwhile, we believe the other two risk factors, a large bile duct and pneumobilia after treatment, can be a cause of primary CBDS as previously reported . Bile flow can be cholestatic in cases with a large common bile duct, and duodenobiliary reflux is present in cases with pneumobilia, both of which can develop primary CBDS.…”
Section: Discussionsupporting
confidence: 67%
“…Meanwhile, we believe the other two risk factors, a large bile duct and pneumobilia after treatment, can be a cause of primary CBDS as previously reported. [20][21][22][23] Bile flow can be cholestatic in cases with a large common bile duct, and duodenobiliary reflux is present in cases with pneumobilia, 24 both of which can develop primary CBDS. The evaluation of primary and secondary CBDS recurrence is essential for prevention of multiple CBDS recurrences, too.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the recurrence rate of CBDS reported ranges between 4 and 25% after ERCP with EST [5]. Ding et al reported recurrent stones after the LCBDE group were lower than the ERCP with laparoscopic cholecystectomy group [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since its first application for bile stone extraction in 1974 [1,2], endoscopic sphincterotomy (EST) has been widely practiced and become a standard therapy in managing choledocholithiasis. However, there are short term and late complications of EST, such as recurrent choledocholithiasis with an incidence of 8.9%~12.3% [3][4][5][6]. Biliary bacteria reflux, surgery or EST, abnormal biliary anatomy, periampullary duodenum diverticulum, and chronic inflammation were the well-established risk factors for recurrent choledocholithiasis [7].…”
Section: Introductionmentioning
confidence: 99%